PENGARUH GOOD CORPORATE GOVERNANCE, KARAKTERISTIK PERUSAHAAN DAN REGULASI PEMERINTAH TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Wandayani Nurfadilah; Yusar Sagara (Department of Accounting-Faculty of Economic and Business (FEB), 2015)
This objective of this study is to examine the good corporate governance,characteristics company and government regulations on the disclosure of corporate socialresponsibility on companies listed in the Indonesia Stock Exchange Period from 2010 to 2014.This study uses secondary data, annual reports obtained from www.idx.com and thecompany's website period 2010-2014. The sampling method of sample selection samplingcluster. The analytical method used is multiple regression analysis which consists of classicalassumption (normality test, multicollinearity, heteroscedasticity test and autocorrelationtest) and test hypotheses (coefficient of determination, t test, F test). The results thatsignificantly influence the audit committee disclosure of CSR while managerial ownership,board size, profitability, liquidity, company profiles and government regulation has no effecton the disclosure of CSR. F Test results showed that the simultaneous effect of independentvariables on the dependent variable.DOI: 10.15408/akt.v8i1.2763